Exploration of the Regulatory Mechanism of Secondary Metabolism by Comparative Transcriptomics in Aspergillus flavus - Yao, Guangshan; Yue, Yuewei; Fu, Yishi; Fang, Zhou; Xu, Zhangling; Ma, Genli; Wang, Shihua (Frontiers in Microbiology, 2018)
Mycotoxins cause a huge threaten to agriculture, food safety, and human and animal life. Among them, aflatoxins have always been considered the most potent carcinogens, and filamentous fungi from Aspergillus genus are their major producers, especially A. flavus. Although the biosynthesis path of these chemicals had been well-identified, the regulatory mechanisms controlling expression of aflatoxin gene cluster were poorly understood. In this report, genome-wide transcriptome profiles of A. flavus from aflatoxin conducing (YES) and non-conducing (YEP) conditions were compared by using deep RNA sequencing (RNA-seq), and the results revealed that aflatoxin biosynthesis pathway and biosynthesis of amino acids were significantly upregulated in YES vs YEP. Further, a novel LaeA-like methyltransferase AFLA_121330 (Lael1) was identified for the first time, to play a specific role in the regulation of aflatoxin biosynthesis. Contrary to LaeA, which gene deletion reduced the level, lael1 deletion resulted in a significant increase in aflatoxin production. Further, co-expression network analysis revealed that mitochondrial pyruvate transport and signal peptide processing were potentially involved in aflatoxin synthesis for the first time, as well as biological processes of ribosome, branched-chain amino acid biosynthetic process and translation were co-regulated by AfRafA and AfStuA. To sum up, our analyses could provide novel insights into the molecular mechanism for controlling the aflatoxin and other secondary metabolite synthesis, adding novel targets for plant breeding and making fungicides.